The Examination of Anti-Money Laundering Laws in Nigeria as International Law Overview - Maruf Adeniyi Nasir (Jurnal Akta, 2022)
The money laundering along with other economic and financial crimes continues to increase unabated. It remains one of the major problems of the country which has retarded immensely its growth and economic development. This research aims to examine the provisions of the current Anti-Money Laundering Act in Nigeria, as the country is under obligation to comply with the international standard, having signed and ratified “Vienna Convention and Palermo Convention”. This research used a doctrinal method which examined and analysed the provision of the Money Laundering (Prohibition) Act 2011. A deducible impression that this created is that it is either those laws are not effective or there is no political will to execute. Combating money laundering therefore requires more than having an array of legal framework. The implementation of those laws is germane for a desire result.